2006
DOI: 10.7589/0090-3558-42.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of Roe Deer, Chamois and Domestic Sheep in the Central Italian Alps

Abstract: ABSTRACT:Roe deer (Capreolus capreolus), chamois (Rupicapra rupricapra rupicapra), and domestic sheep in the Orobie Alps, Italy, were serologically tested for antibodies to selected pathogens that may be transmitted across species. Antibodies against Brucella spp. and bovine herpesvirus 1 (roe deer and chamois only) were not detected in any species. In roe deer, antibodies were detected against Toxoplasma gondii (13%) and Neospora caninum (3%). Chamois tested positive for antibodies to T. gondii (5%), N. canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 13 publications
(11 reference statements)
7
54
0
1
Order By: Relevance
“…With respect to the age of subject animals, the observed RSV seroprevalence of 47% in adult sheep is similar to that reported for Italian sheep in 2000, with 42% [13] and in sheep under a mixed flock system in Peru, with 49.3% [1]. Another study in sheep from Syria reported a higher prevalence, with 63.6% [13].…”
Section: Resultssupporting
confidence: 82%
“…With respect to the age of subject animals, the observed RSV seroprevalence of 47% in adult sheep is similar to that reported for Italian sheep in 2000, with 42% [13] and in sheep under a mixed flock system in Peru, with 49.3% [1]. Another study in sheep from Syria reported a higher prevalence, with 63.6% [13].…”
Section: Resultssupporting
confidence: 82%
“…Little is known about chlamydiosis in wild ruminants, although serologic investigations in Europe suggest a role for wild ruminants as a chlamydial wildlife reservoir (Andreani et al, 1986;Giovannini et al, 1988;Cordier, 1991;Dedek et al, 1991;Cubero-Pablo et al, 2000;Gaffuri et al, 2006). Most studies detected genus-specific antibody response because investigators usually used the complement fixation test (CFT).…”
Section: Introductionmentioning
confidence: 99%
“…In alpine chamois, high antibody prevalence against BVDV was found in serologic surveys in Italy and Germany (Kleinschmidt, 2004;Gaffuri et al, 2006). Current investigations in Austrian chamois (n599) from the region of Tyrol could not give any evidence to Pestivirus infection in this species (Ignasi, pers.…”
mentioning
confidence: 99%